STATUS HUKUM PEGAWAI PERUSAHAAN DAERAH DALAM POLA HUBUNGAN KERJA PEMERINTAH DAERAH DENGAN BUMD - Rizki Ramadhani; Rizki Maharani (SOL JUSTICIA, 2021)
This study discusses regional employees who have different legal positions and statuses from one another. The purpose of this study was to find out the legal status of regional company employees in the working relationship of the regional government and Regional Owned Enterprises (BUMD). The research method used is normative juridical which focuses on the application of regulations regarding BUMD and local governments in determining the legal status of employees. A regional company greatly determines the implementation of regional companies through determining the legal status in the form of PKWT and PKWTT based on the laws and regulations governing the legal status of employees in regional companies. The position and legal status of each regional employee will determine the rights and obligations that will be received by regional company employees.